The Association Between Religiosity, Spirituality, and Medication Adherence Among Patients with Cardiovascular Diseases: A Systematic Review of the Literature - Elhag, Marwa (Journal of religion and health, 2022)
This systematic review aimed to summarize the literature on the relationship between religiosity or spirituality (R/S) and medication adherence among patients with cardiovascular diseases (CVDs) and to describe the nature and extent of the studies evaluating this relationship. Seven electronic databases (PubMed, MEDLINE, EMBASE, Scopus, the Cochrane Central Library, ProQuest Theses and Dissertations, and Google Scholar) were searched with no restriction on the year of publication. The Crowe Critical Appraisal Tool was used to evaluate the methodological quality of the eligible studies. Due to the heterogeneity observed across the included studies, data synthesis was performed using a narrative approach. Nine original studies published between 2006 and 2018 were included in the review. Only a few quantitative studies have examined the relationship between R/S and medication adherence among patients with CVDs. Most studies were conducted in the USA (n = 7) and involved patients with hypertension (n = 6). Five studies showed a significant correlation between R/S (higher organizational religiousness, prayer, spirituality) and medication adherence and revealed that medication adherence improved with high R/S. The other four studies reported a negative or null association between R/S and medication adherence. Some of these studies have found relationships between R/S and medication adherence in hypertension and heart failure patients. This review showed a paucity of literature exploring the relationship between R/S and medication adherence among patients with other CVDs, such as coronary artery diseases, arrhythmia, angina and myocardial infarction. Therefore, the findings suggest that future studies are needed to explore the relationship between R/S and medication adherence among patients with other types of CVDs. Moreover, there is a need to develop interventions to improve patients’ medication-taking behaviors that are tailored to their cultural beliefs and R/S.